ANALISIS KEPUASAN PELAYANAN DOKUMEN KEPENDUDUKAN DI KABUPATEN RAJA AMPAT PROVINSI PAPUA BARAT 2009 - , Syaiful Mahmud Sangadji, Drs.; , Dr. Soeranto, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to know as for as the result of Demography Document has operated by Department of civil Registration and Demography of Raja Ampat Regency. To analize delivering performance of civil Registration and Demography Department of Raja Ampat regency in giving service according to components of factors or attributes to the societys satisfaction and how the important/ aspiration that experienced by society in Raja Ampat Regency, to reflect with reability, responsiveness, confidente, emphaty and tangible to know about the quality of service. To determine the quality of service to the society, to use description, quality and quantity method (Analysis the degree of societys satisfaction performance and importance), and diagram kartesius, to analize primary date gained from 175 respondents receiver the service of Demography Document in Department of civil Registration and Demography of Raja Ampat Regency, by scale likert (Five Grades). Result of research received service quality has operated according to hope, be desirable the performance has operated constanly of defend by Department of Civil Registrtion and Demography, and importance/ aspiration of still to attention.